AB0052 Treatment with bactericidal/permeability-increasing protein reduces crystal-induced inflammation and collagen-induced arthritis in mice. (12th June 2018) - Scanu, A.; Luisetto, R.; Raffeiner, B.; Corain, L.; Galozzi, P.; Ramonda, R.; Oliviero, F.; Punzi, L.
Abstract : Background: Bactericidal/permeability-increasing protein (BPI) is an antibacterial glycoprotein produced by polymorphonuclear cells (PMN). Although BPI has been detected in synovial fluid of patients with different type of arthritis, its effects in these diseases remain unexplored. Objectives: To investigate the effects of BPI in mouse models of crystal-induced inflammation and collagen-induced arthritis (CIA). Methods: Air pouches were raised on the backs of CD1 mice (n=14 per condition). 2 mg of calcium pyrophosphate (CPP) crystals in 1 ml of PBS were injected into the pouch in the presence or absence of 0.1 mg of BPI for 3 hour. Controls received 1 ml of PBS. After the sacrifice, pouch fluids were recovered by washing with 2 ml of PBS. Leukocyte count in lavage fluids was obtained using a hemocytometer and the PMN percentage was determined by May-Grünwald-Giemsa staining. CIA was induced in C57Bl/6 mice (n=12 per condition) by immunisation with collagen/complete Freund's adjuvant emulsion at days 0 and 21. Arthritis was monitored by measuring paw swelling with a calliper and scored (0–5) every 2 days. Arthritic mice (paw score=2) were intraperitoneally injected with 200 µl of BPI (50 µg/ml) or vehicle only (PBS). Treatment and arthritis evaluation were carried out twice a week for 2 month. At the experiment endpoints, mice were subjected to knee and ankle ultrasound (US) and then euthanized. Hind paws were processed for histological analysis to assess inflammation, pannus formation, cartilage and bone destruction in knee and ankle joints (score 0–5). IL-1β, IL-6, CXCL1 and TNF levels were measured by ELISA in pouch fluids and serum from collected blood. Results: The injection of CPP crystals into the pouches induced leukocyte infiltration (26.27±4.14 × 10 5 cells/ml) comprising 73.5%±2.12% of PMN. IL-1β (80.99±3.65 pg/ml), IL-6 (892.90±28.14 pg/ml), CXCL1 (762.82±50.08 pg/ml) and TNF (52.70±0.49 pg/ml) were measured in lavage fluids. The co-injection of crystals and BPI inhibited leukocyte influx by 67% and PMN infiltration by 55% and, in turn, the levels of all assessed cytokines were reduced (46% IL-1β, 35% IL-6, 60% CXCL1, 64% TNF). CIA mice reached an arthritis score of 2 after 28–33 days and showed a progressive worsening of clinical signs that picked at day 49–56, and then improved only in BPI group. At the end of the experiment, hind paw swelling and scores were lower in BPI-mice (paw thickness=4.76±0.33 mm; score=4±0.5) than in controls (paw thickness=6.39±0.95 mm; score=5). US revealed synovial hypertrophy in all joints considered, but the presence of effusion only in knees of untreated animals. Power Doppler was positive in controls but not in BPI group. BPI decreased histological scores for pannus formation and inflammation by 3-fold, and for cartilage and bone destruction by 2-fold as compared to PBS-mice. CIA induction led to high levels of IL-1β (656.80±45.6 pg/ml), IL-6 (376.04±46.33 pg/ml), CXCL1 (834.08±68.8 pg/ml) and TNF (277.72±15.24 pg/ml), which were reduced with BPI treatment by 66%, 46%, 47% and 93%, respectively. Conclusions: This study shows inhibitory effects of BPI on crystal-induced inflammation and CIA, suggesting a therapeutic potential of this protein for arthritis by down-regulating inflammatory process. Disclosure of Interest: None declared